Сoncept of developmental education mathematics: didactic model of teaching and mathematical activity of students - Семенець, Сергій Петрович (Pedagogy of Higher and Secondary Education, 2019)
Semenets S. P. Сoncept of developmental education mathematics: didactic model of teaching and mathematical activity of students. In the context of personal and developmental approach analyzes the methods of teaching mathematics, nonlinear created didactic model of teaching and mathematical foundations of the students. The results of content analysis and theoretical modeling developed didactic-of task of developing a method of teaching mathematics.